Incinerator Sebagai Solusi Efektif Kurangi Polusi Udara untuk Mewujudkan Lingkungan Hidup Sehat - Okatiyana Okatiyana; Farrel Jilal Chisan; Brimas Rijal Maulana; Ajeng Rahayuningtyas; Muhamad Saiful Rozaq; Arselin Arifina Alanis; Adelia Putri Oktavia Ramadani; Hani Putri Safira; Salsabila Poetri Dariyah; Kevin Aqila Arfa Reza (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2025)
Tawangsari Hamlet, Tejosari Village, Ngablak District, Magelang Regency, faces serious waste management challenges, reflected in the high daily waste production and the inactivity of waste banks post-COVID-19. To address this issue, the Tidar University Community Service Program (KKN) was implemented, aiming to improve environmental cleanliness through active community participation. This program also supports the achievement of the "Climate Action" goal in the Sustainable Development Goals (SDGs), which focuses on combating climate change caused by air pollution and reducing environmental pollution. The method used in this program is Participatory Action Research (PAR), which is oriented towards community empowerment by involving all stakeholders in every stage of implementation. The activity began with a series of observations to understand the condition of waste management in the community. Then, a waste management tool was created in the form of a smoke-free waste incinerator, which aims to manage inorganic waste in an environmentally friendly manner. In addition, trash bins to facilitate waste sorting at the household level were also provided. Socialization and mentoring for the community, especially youth organizations, were carried out to introduce and educate them on the correct use of incinerators and waste sorting. A demonstration of incinerator use was also conducted with the community, which proved to increase understanding and active participation. The implementation of the incinerator and waste sorting facility demonstrated that these measures were effective in addressing the waste problem in Tawangsari Hamlet and contributed to a cleaner and healthier environment. Furthermore, the program successfully raised environmental awareness among the Tawangsari Hamlet community. Through direct involvement in the waste management process, residents not only gained new knowledge about the importance of waste sorting but also experienced the direct benefits of implementing smoke-free incinerator technology.Keywords: waste management, low-smoke incinerator, Climate Action, SDGs, community empowerment, environmental pollution, Magelang Regency